Dynamic adjustment in open economies - Jürgen Meckl (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1990)
This paper analyzes adjustment to exogenous shocks in a dynamic version of the specific-factors model in which capital is assumed to be a quasi-fixed factor. Capital allocation is treated as an issue in investment theory, thus endogeniz-ing long-run capital stocks of industries. Convex costs of adjustment generate finite Keynesian investment demand functions which are incorporated in a two-sector trade model. Depending on the source of the exogenous shock comparative static effects are ambiguous and the adjustment path to the long-run equilib-rium may be characterized by an overadjustment of capital stocks and/or of the national product. The long-run equilibrium is almost always characterized by non-equalization of capital rentals.
Keywords: 330; Offene Volkswirtschaft; Wirtschaftliche Anpassung; Theorie